Perform, Repeat, Record : Live Art in History. - Jones, Amelia; Heathfield, Adrian (Intellect, 2012)
Bringing together contributors from dance, theatre, visual studies, and art history, Perform, Repeat, Record addresses the conundrum of how live art is positioned within history.